Interdisciplinary perspectives on international law and international relations : the state of the art - Dunoff,Jeffrey L,Ed (Cambridge, 2013)
"This book brings together the most influential contemporary writers in the fields of international law and international relations to take stock of what we know about the making, interpretation and enforcement of international law"--